Clinical efficacy of IgM-enriched immunoglobulin as adjunctive therapy in neonatal and pediatric sepsis: a systematic review and meta-analysis - Dinleyici, Ener Cagri; Frey, Georg; Kola, Ermira; Wippermann, Ulrike; Bauhofer, Artur; Staus, Alexander; Griffiths, Peter; Azharry, Muhamad; Rohsiswatmo, Rinawati (Frontiers in Pediatrics, 2023)
Background: Sepsis is a major cause of mortality and morbidity globally, with around one-quarter of all sepsis-related deaths occurring in children under the age of 5. We conducted a meta-analysis and systematic review of the literature to evaluate the clinical effectiveness of an IgM-enriched immunoglobulin preparation in pediatrics and neonates with sepsis. Methods: Systematic searches of PubMed, the Cochrane Library and Embase databases were performed in November 2022, with no date limitations, to identify studies in which IgM-enriched immunoglobulin was used as adjunctive therapy in neonatal and pediatric patients with sepsis. Results: In total, 15 studies fulfilled the eligibility criteria, 13 neonatal studies and 2 pediatric studies. Pooled estimates from all studies indicated that mortality rates were significantly lower in patients who received treatment with the IgM-enriched immunoglobulin compared with controls (OR 0.41; 95% CI 0.32–0.55). Further analyses in neonatal studies, alone, showed a significant benefit with longer treatment durations (>3 days) versus the recommended treatment duration (3 days) (OR 0.32; 95% CI 0.22–0.47) vs (OR 0.61; 95% CI 0.41–0.92). Treatment with IgM-enriched immunoglobulin was associated with a lower mortality risk compared with controls in prospective studies versus retrospective analyses (OR 0.37; 95% CI 0.27–0.51) vs (OR 0.73; 95% CI 0.41–1.30). Conclusions: This systematic review suggests that adjunctive treatment with IgM-enriched immunoglobulin may reduce the risk of mortality in neonatal and pediatric populations. However, large randomized controlled trials are required to further substantiate and evaluate these findings.